Genetics of resistance to Fusarium wilt in castor caused by Fusarium oxysporum f. sp . ricini - Lavanya, C.; Raoof, M.A; Santha Lakshmi Prasad, M. (Indian Phytopathology, 2011)
Wilt caused by Fusarium oxysporum f. sp . ricini is a major problem in all castor growing areas of India leading to heavy loss of plant population of susceptible varieties in different stages of the crop. Six generations of three crosses of castor were evaluated in the wilt sick plot to study the genetics of wilt resistance. The disease resistance in F1 of the cross VP-1 x 48- 1 indicated that resistance to Fusarium wilt is recessive while in the other two crosses, DCP 13 / RG 297 and DPC 9 / RG 297 resistance is incompletely dominant. The cross DPC 9 x RG 297 involving both resistant parents gave higher level of resistance compared to the other two crosses involving one resistant parent. The inheritance of resistance to wilt is governed by oligogenes with epistatic interactions. Haymans scaling test indicated that both allelic and nonallelic interactions were significant for inheritance of the trait.